Pendampingan Optimasi Daerah Resapan Guna Menangani Genangan di Kota Bojonegoro - Indriani, Yulia; Zainuddin, Zainuddin; Utomo Putri, Levinta Marrietha (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Urban waterlogging is a persistent environmental issue in rapidly developing areas such as Bojonegoro, Indonesia, driven by land cover change, inadequate urban drainage systems, and increasing climate variability. This study introduces a nature-based solution (NBS) approach involving the implementation of boezem (retention ponds) and infiltration wells to mitigate urban flooding risks. The community service program aimed to enhance the technical capacity of local agencies and promote evidence-based planning using EPA-SWMM hydrological modeling. The methodology included stakeholder outreach, participatory mapping, technical training sessions, and the construction of pilot infiltration infrastructures. The outcomes demonstrate significant improvements in institutional technical understanding, the establishment of a priority zone map for infiltration development, and the successful design and deployment of pilot-scale boezem and infiltration wells, validated through post-construction hydrological monitoring. Despite challenges such as limited funding and the lack of regulatory mandates, the findings suggest that participatory, model-informed NBS strategies can offer scalable, adaptive, and sustainable urban flood mitigation solutions.